Development of an enterprise excellence index for indonesian state-owned enterprises using anp method - Sulistyo, Budi (2022)
State-owned enterprises (SOEs) have retained a strong presence in the Indonesian economy and play an essential role in providing vital infrastructure and public services. Furthermore, the Indonesian government demands SOEs to be more competitive locally and globally. To accomplish this, all 114 SOEs are committed to a business excellence model known as the measurement criteria for performance excellence or Kriteria Penilaian Kinerja Unggul (KPKU). To ensure effective measurement and minimise the complexity aspects of performance assessment, it is essential to identify factors that determine the SOE's performance measurement results. So, in this research, an enterprise excellence index (EEI) for Indonesian SOEs is developed. The study is carried out with the following objectives: investigate the implementation level of the KPKU program in Indonesian SOEs through an exploratory survey, analyse a scale of priorities for the EEI criteria using the analytic network process (ANP) method, and develop the EEI for Indonesian SOEs. The exploratory survey reveals that respondents from 30 SOEs provided a positive responses related to the KPKU implementation. In order to improve the effectiveness of the measurement, the index should be developed to reflect the Indonesian SOEs’ context. Subsequently, 21 experts were involved in the modified ANP pairwise judgement process to build a framework for the EEI network and calculate the index weights, resulting in a refined composition of the index with high consistency ratios. Finally, an evaluation survey involving seven experts was undertaken to determine the priority weights of categories and items of the EEI. The number of scores was different from the KPKU for the categories of Customer, Measurement, analysis and knowledge management, Workforce, and Results. Based on these findings, the EEI for Indonesian SOEs is suggested as a self-assessment approach for measuring performance according to Indonesian context.